PENGARUH CURRENT RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PT XL AXIATA Tbk PERIODE 2014-2023 - Rosa Nurlita; Sutiman (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of Current Ratio (CR) and Return on Equity (ROE) on Stock Prices at PT XL Axiata Tbk for the period 2014-2023. The method used is a descriptive statistical analysis study with a quantitative approach. This study uses secondary data obtained from the annual financial statements of PT XL Axiata Tbk for the period 2014-2023. The analysis techniques used include classical assumption tests, multiple linear regression analysis, T tests, F tests, determination tests, and correlation coefficient tests with data processing using the SPSS 29 statistical program. The results of the study simultaneously show that the variables Current Ratio (CR) and Return on Equity (ROE) have a positive and significant effect on Stock Prices with a calculated f value of 4.814> 4.74 and a Sig value of 0.048 <0.05. Partially, the Current Ratio (CR) variable has a positive and significant effect on Stock Price with a t-value of 3.099 > 2.36462, and a significance level of 0.017 < 0.05. Return on Equity (ROE) has a negative and insignificant effect on Stock Price with a t-value of -0.428 < 2.36462, and a significance level of 0.681 > 0.05. Based on the results of the determination coefficient analysis, the R square value is 0.579, so the Current Ratio (CR) and Return on Equity (ROE) contribute 57.9% to Stock Price while the remaining 42.1% is influenced by other factors not studied.